The effect of regular aerobic exercise on renal function in patients with CKD: A systematic review and meta-analysis - Ma, Qirui; Gao, Ye; Lu, Jiandong; Liu, Xinhong; Wang, Ruolin; Shi, Yajun; Liu, Jingqi; Su, Hao (Frontiers in Physiology, 2022)
Objective: To evaluate the effect of regular aerobic exercise on the improvement of renal function in patients with chronic kidney disease through meta-analysis and to provide targeted exercise recommendations for patients with CKD. Methods: PubMed, Web of Science, EBSCO, China National Knowledge Infrastructure (CNKI), and other databases were searched, and randomized controlled trials on the effects of regular aerobic exercise on renal function-related indexes in patients with CKD were collected according to the inclusion and exclusion criteria. The methodological quality of the included literature was evaluated using the Cochrane evaluation tool second generation, and statistical analysis was performed using R analysis software. Results: A total of 12 randomized controlled trials (RCTs) with a total of patients with CKD were included, and the results of the meta-analysis showed that regular aerobic exercise significantly improved the estimated glomerular filtration rate SMD = 0.65, 95% CI [0.30, 1.00], serum creatinine SMD = -0.63, 95% CI [-0.86, -0.40], 24-h urine protein volume in patients with CKD SMD = -0.41, 95% CI [-0.70, -0.11], and serum urea nitrogen SMD = -0.66, 95% CI [-1.20, -0.12]. Single exercise session longer than 30 min significantly improved the estimated glomerular filtration rate in CKD patients (p < 0.01), and walking and running as exercise modalities significantly improved CKD patients’ SCr levels were significantly improved by walking and running as exercise modalities (p < 0.05), and the improvement effect was not significant when cycling was selected as an exercise modality. Conclusion: Regular aerobic exercise has a significant effect on the estimated glomerular filtration rate, serum creatinine, 24-h urine protein amount, and blood urea nitrogen in CKD patients. Aerobic exercise with a single exercise duration longer than 30 min has a more significant effect on the estimated glomerular filtration rate, and aerobic exercise by walking or running can more effectively improve the serum creatinine in CKD patients.